Adaptation of Islamic Criminal Law in Facing Digital Economic Crime in the Era of Technological Disruption - Fikri, Ahmad Lutfi Rijalul (Istinbath : Jurnal Hukum, 2024)
The rapid development of digital technology has significantly impacted various aspects of life, including the economy, but it has also given rise to complex digital economic crimes. This research examines the adaptation of Islamic criminal law in facing the challenges of digital economic crimes, such as online fraud, money laundering, and skimming. The method used is qualitative with a descriptive-analytical approach, relying on literature and official documents. The research findings indicate that Islamic criminal law needs to update its definitions and classifications of crimes to include actions in the digital space and apply principles of justice, prevention, rehabilitation, legal certainty, and limitations on punishment. In addition, using technology in law enforcement and international cooperation is crucial in addressing transnational crime. With a comprehensive approach, Islamic criminal law can serve as an effective tool in creating a safer and more just society in the era of technological disruption.